Macro-Agriculture in the 21st Century China –An Answer to Lester Brown’s Three Questions - , Li Kangmin (Archives of Current Research International, 2017)
Lester Brown asked “Who will feed China?” 20 years ago and asked “Can the United States Feed China? In March 2011 and wrote another article “Can the World Feed China?” in 25 Feb 2014. China is facing two problems: one, population. It is estimated that China's national grain consumption would reach 572.5 million tons by 2020. Although China is largely self sufficient in staple food, it is not in soybeans and corn. When income on average increases, the people need to eat better, to be healthier. How can China feed herself? She should adopt Chinese model. Her economic model must consider resources and environmental carrying capacity in China. China must register zero growth of population in 2030; energy and resources consumption rate in 2040; eco-environmental degradation rate in 2050. The papers retrospect small agriculture, modern agriculture and macro agriculture in China. We must inherit the fine tradition but encourage innovation. Three cases can indicate how to follow up the Tao of agriculture: First, Grain production in moderate scale in Gansu Autonomous Region; second, new discovery of Sea Rice 86 as a special cultivar, and Yuan Longping’s super rice yield more than 1500 kg per mu; third, planting rice in arable desert; and new aquaponics technology as reserve resources.